Being(s) in the World: Navigating the Macro Changes in Pastoral Theology in a Neo-Liberal Age - Reddie, Anthony G. (International journal of practical theology, 2021)
This review article focusses on three new texts in Pastoral theology, each of which, offers an important and interesting turn in the discipline. The three texts - Caring For Souls in a Neo-Liberal Age , by Bruce Rogers-Vaughn 1 , Race, Religion, and Resilience in the Neo-Liberal Age , by Cedric C. Johnson 2 and Care of Souls, Care of Polis by Ryan Lamothe 1 - will be reviewed in light of the prevailing themes they share. In what ways are these three authors foregrounding important new dimensions in the study of Pastoral theology and Pastoral care?